Room-temperature photoluminescence in amorphous SrTiO3-The influence of acceptor-type dopants - Soledade, L. E B; Longo, Elson [UNESP]; Leite, E. R.; Pontes, F. M.; Lanciotti, F.; Campos, C. E M; Pizani, P. S.; Varela, José Arana [UNESP] (My University, 2002)
Room-temperature photoluminescence (PL) was observed in undoped and 2 mol% Cr-, Al- and Y-doped amorphous SrTiO3 thin films. Doping increased the PL, and in the case of Cr significantly reduced the associated PL wavelength. The optical bandgaps, calculated by means of UV-vis absorption spectra, increased with crystallinity and decreased with the doping level. It was considered that yttrium and aluminum substituted Sr2+, whereas chromium replaced Ti4+. It is believed that luminescence centers are oxygen-deficient BO6 complexes, or the same centers with some other defects, such as oxygen or strontium vacancies, or BO6 complexes with some other defects placed in their neighborhood. The character of excitation and the competition for negatively charged non-bridging oxygen (NBO) among numerous types of BO6 defect complexes in doped SrTiO3 results in various broadband luminescence peak positions. The results herein reported are an indicative that amorphous titanates are sensitive to doping, which is important for the control of the electro-optic properties of these materials. The probable incorporation of Cr into the Ti site suggests that the existence of a double network former can lead to materials displaying a more intense photoluminescence.
Keywords: Absorption spectroscopy; Amorphous materials; Composition effects; Crystal defects; Crystalline materials; Doping (additives); Electrooptical effects; Numerical analysis; Photoluminescence; Substitution reactions; Temperature; Ultraviolet spectroscopy; Acceptor type dopants; Nonbridging oxygen; Strontium titanate; Strontium compounds